Extensive polymorphism and evidence of selection pressure on major histocompatibility complex DLA‐DRB1, DQA1 and DQB1 class II genes in Croatian grey wolves. Issue 1 (8th November 2012) - Arbanasić, H.; Huber, Đ.; Kusak, J.; Gomerčić, T.; Hrenović, J.; Galov, A.
Abstract The genes of the major histocompatibility complex (MHC) are a key component of the mammalian immune system and have become important molecular markers for measuring fitness‐related genetic variation in wildlife populations. Because of human persecution and habitat fragmentation, the grey wolf has become extinct from a large part of Western and Central Europe, and remaining populations have become isolated. In Croatia, the grey wolf population, part of the Dinaric–Balkan population, shrank nearly to extinction during the 20th century, and is now legally protected. Using the cloning–sequencing method, we investigated the genetic diversity and evolutionary history of exon 2 of MHC class II DLA‐DRB1, DQA1 and DQB1 genes in 77 individuals. We identified 13 DRB1, 7 DQA1 and 11 DQB1 highly divergent alleles, and 13 DLA‐DRB1/DQA1/DQB1 haplotypes. Selection analysis comparing the relative rates of non‐synonymous to synonymous mutations (dN/dS) showed evidence of positive selection pressure acting on all three loci. Trans‐species polymorphism was found, suggesting the existence of balancing selection. Evolutionary codon models detected considerable difference between alpha and beta chain gene selection patterns: DRB1 and DQB1 appeared to be under stronger selection pressure, while DQA1 showed signs of moderate selection. Our results suggest that, despite the recent contraction of the Croatian wolf population, genetic variability in selectively maintained immune genes has been preserved.